Administrative reforms and the rule of law : case law analysis as an inspiration for the Slovene reorganisation of social work centres - Babšek, Matej (Array, 2020)
Designing a public governance model suitable for a particular task often lacks an empirical basis for change and the criteria for evaluation. Hence, the paper analyses the case law following from the decisions of social work centres (SWC) in Slovenia in order to gain insight in the lawfulness of their work as a key component of the rule of law and thus pinpoint the optimal framework for improvements. Using quantitative and qualitative analyses of 213 higher court judgments issued in the course of five years, the paper examines, by means of content analysis, which elements of the rule of law are the most problematic in practice. There is special emphasis on lawfulness and equality in substantive terms and on fair trial in procedural terms. The case law following from the SWC cases in the highest courts in Slovenia is quite consistent, but it does reveal certain gaps. These gaps need to be bridged on both regulatory and implementation levels in terms of clearer and yet not too rigid rules, recognition of participative procedural standards, and more flexible organisation. The case law thus indicates options for legislative changes and administrative reforms of the Slovene welfare system and beyond.